The Influence Of Intellectual Capital And Innovative Work Behaviour To Business Performance Cigondewah Textil Bandung - Muhammad Firza Firdaus; Trustorini Handayani; Eddy Jusuf; Undang Juju; Chucum Sumiarty (International Journal of Management Research and Economics, 2024)
This research was conducted on business actors in the Cigondewah Textile Bandung. This study aims to examine the effect of Intellectual Capital and Innovative Work Behavior on Business Performance. The method used in study is to use descriptive analysis. The sampling technique uses non-probability sampling which is a saturated sampling type. Data collection techniques used are techniques through interviews, literature, and questionnaires. The analysis used in this study is multiple linear analysis. The results of this study indicate that Intellectual Capital and Innovative Work Behavior on Business Performance have a significant or positive effect on Cigondewah Textile Bandung